TYPOLOGICAL FEATURES OF THE CATEGORY OF VOICE IN ENGLISH AND KARAKALPAK LANGUAGES - Satullaeva Nargiza Jalgasbaevna (Galaxy International Interdisciplinary Research Journal, 2023)
This article deals with morphological and syntactical meaning of category of Voice on the basis of English and Karakalpak languages which are expressed by the relation of the subject and object.